PERBEDAAN PENGARUH METODE PEMBELAJARAN PROBLEM BASED LEARNING DAN COOPERATIVE LEARNING TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS DALAM MATA AJAR KEPERAWATAN MEDIKAL BEDAH MAHASISWA SEMESTER III - Dwi w, Binarti (JURNAL KEPERAWATAN SEHAT, 2014)
Background of the researchCritical thinking abilities that will enhance students ability to achieve expected competencies , also need a good motivation to improve the ability to think critically influenced by the teaching methods adopted by the educational institution in which the student study space , so that the learning process can be well received by students .Research PurposeThis study aimed to analyze the differences in the influence of learning methods Problem Based Learning with Cooperative Learning on the motivation and ability to teach critical thinking in the lesson Medical Surgery of the respiratory system .MethodThis study is the True Experimental design , implemented in Nursing Academy Bina Sehat PPNI Mojokerto . Consisted of 121 respondents with a sampling technique Randomized control trial .Research instruments is questionnaire. That is about the learning motivation and the ability to think critically . All declared valid and reliable .Analysis of the data analysis using Kruskall Wallis test and to compare between groups using the Mann Whitney .Result of the researchThere are differences in the effect of problem-based learning instructional methods and cooperative learning on learning motivation demonstrated by the Kruskal-Wallis test with significant values (p <0.016), while the ability to think critically Kruskall Wallis test results show the value (p <0.00) in the Healthy Development of Nursing Academy students PPNI district Mojokerto.Setelah several variables studies conducted with the Mann-Whitney statistical test results on critical thinking ability differences are statistically significant effect between learning methods Problem Based Learning with Conventional differences were highly significant effect (p <0.00), whereas Motivation learning differences that are statistically significant effect between learning methods Problem based learning with cooperative learning (p <0.005).ConclusionThere are differences that are statistically significant effect on the learning methods Problem Based Learning and Cooperative Learning in the ability to think kritis.Ada differences influence learning methods Problem Based Learning and Cooperative Learning on student learning motivation in the eyes of Medical Surgery Nursing teaching Healthy Development PPNI MojokertoKeywords :learning methods , Problem Based Learning , Cooperative Learning , conventional , learning motivation, the ability to think